Analisis Kesulitan Siswa dalam Menyelesaikan Soal Cerita Perkalian pada Kelas III Sekolah Dasar - Syalshabil Shafa Pranata; Cholis Sa’dijah; Lathiful Anwar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Students often encounter errors in calculating multiplication, especially those who lack a grasp of the basic concepts of multiplication. This is compounded by the independent curriculum, which forces students to become accustomed to learning mathematics while developing literacy, commonly referred to as numeracy literacy. Many factors contribute to students' difficulties in solving math story problems in multiplication, including a lack of comprehension due to inattention in reading the problem, a lack of understanding of the concept of multiplication, and a lack of fluency in reading. Furthermore, there is limited variety in learning activities and media. These difficulties can be overcome if teachers actively provide more multiplication problems in the form of numeracy literacy story problems and provide engaging learning experiences for students through innovative, appropriate and concrete learning media. Students must also be enthusiastic about continuing to learn and actively participate in learning. Therefore, learning mathematics in the form of story problems requires a holistic approach that considers literacy skills, conceptual understanding, and the need for varied learning to support the implementation of numeracy literacy in the Independent Curriculum.